2019
DOI: 10.1111/tbed.13149
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation and phylogenetic analysis of caprine parainfluenza virus type 3 in sheep of China

Abstract: Caprine parainfluenza virus type 3 (CPIV3) is a new member of the Respirovirus genus in the Paramyxivirudae family, mainly causing respiratory disease. Up to now, accumulating evidence has focused on CPIV3 infection in goats, with little understood about its epidemiology in sheep. To that end, we collected 1,163 sheep sera samples from nine provinces/autonomous regions in 2012 and 1,863 samples from six provinces/autonomous regions during 2016–2017, with serological prevalence of 50.3% (95% CI: 47.5, 53.3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Since its discovery, CPIV3 has caught the attention of researchers in goat and sheep respiratory diseases due to its high prevalence and pathogenicity. Our previous report showed that CPIV3 antibody could be detected in 39.3% ( 2 ) and 64.9% ( 3 ) of 2,919 goat sera and 1,863 sheep sera, respectively, collected from six provinces in China. Moreover, CPIV3 genomes were frequently detected in clinical samples using real-time qPCR ( 4 ).…”
Section: Introductionmentioning
confidence: 98%
“…Since its discovery, CPIV3 has caught the attention of researchers in goat and sheep respiratory diseases due to its high prevalence and pathogenicity. Our previous report showed that CPIV3 antibody could be detected in 39.3% ( 2 ) and 64.9% ( 3 ) of 2,919 goat sera and 1,863 sheep sera, respectively, collected from six provinces in China. Moreover, CPIV3 genomes were frequently detected in clinical samples using real-time qPCR ( 4 ).…”
Section: Introductionmentioning
confidence: 98%
“…CPIV3 causes severe respiratory diseases, characterized by the clinical symptoms as coughing, nasal discharges, viremia, virus shedding and lung consolidation [18]. The virus infects sheep and goats, and has been found in many provinces in China with an overall seroprevalence of 39.3-64.9 % [19,20]. The mechanism of pathogenesis and transmission of CPIV3 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of complete L protein amino acid sequences, representing the current species demarcation criterion for Respirovirus genus [26], shows that ChamoisRV/IT2014 possesses sequence differences from the other respirovirus species. Moreover, although the phylogenetic analysis of ChamoisRV/IT2014 based on M, HN and F genes, used as targets for genetic typing of RV3 [5], confirms the highest nucleotide identity with CRV3, it shows low nucleotide identity for all three genes.…”
Section: Discussionmentioning
confidence: 85%
“…CRV3 (formerly CPIV3) was first identified in goats [2] and recently also in sheep in China [5]. To date, CRV3 has not been reported in other countries.…”
Section: Introductionmentioning
confidence: 99%